Drop-off drug distribution: why users choose to source illegal drugs from delivery dealers. Issue 2 (3rd July 2019) - Søgaard, Thomas Friis
ABSTRACT: While drug dealing organized as drop-off delivery services is not a new phenomenon, research indicates that it is on the rise. The European Monitoring Centre for Drugs and Drug Addiction recently described how the European cocaine market is undergoing a process of '[u]bernisation', where more sellers promote additional services beyond the product itself, such as 'fast delivery anywhere at any time'. Based on the assumption that developments in retail-level drug distribution are fuelled by supply-side as well as demand-side processes, this paper reports key findings from a qualitative study in Denmark exploring user motivations for purchasing drugs from drop-off delivery dealers.